2018
DOI: 10.3389/fpsyg.2018.00173
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Is Associated with a Reduction of the Oxytocin Receptor in Peripheral Blood Mononuclear Cells

Abstract: Background: Child maltreatment (CM) and attachment experiences are closely linked to alterations in the human oxytocin (OXT) system. However, human data about oxytocin receptor (OXTR) protein levels are lacking. Therefore, we investigated oxytocin receptor (OXTR) protein levels in circulating immune cells and related them to circulating levels of OXT in peripheral blood. We hypothesized reduced OXTR protein levels, associated with both, experiences of CM and an insecure attachment representation.Methods: OXTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
5
29
0
1
Order By: Relevance
“…Due to its short circulating half-life [37], basal Oxt plasma levels might have normalized in adulthood after ELS exposure. In fact, our finding is in good agreement with our previous study in women with CM experiences, whose basal Oxt plasma levels were unchanged in adulthood [38], and another study also showing that Oxt plasma levels are independent of the dose of maltreatment [39]. Nevertheless, this does not exclude that ELS may exert a "programming" effect on acute Oxt release during stress challenges at later life periods.…”
supporting
confidence: 92%
“…Due to its short circulating half-life [37], basal Oxt plasma levels might have normalized in adulthood after ELS exposure. In fact, our finding is in good agreement with our previous study in women with CM experiences, whose basal Oxt plasma levels were unchanged in adulthood [38], and another study also showing that Oxt plasma levels are independent of the dose of maltreatment [39]. Nevertheless, this does not exclude that ELS may exert a "programming" effect on acute Oxt release during stress challenges at later life periods.…”
supporting
confidence: 92%
“…This is consistent with results from a large Norwegian study in preschoolers, which extends these results by showing that the association pattern between PA and motor competence is characterized particularly by vigorous intensities (Nilsen et al, 2019a). Importantly, motor competence will likely not be optimally stimulated through naturally occurring behaviors and thus needs to be taught (Stodden et al, 2008;Robinson et al, 2016). Furthermore, to optimally promote motor competence, it is important to provide challenging activities that keep the children on a positive trajectory of learning and maximize motivation and engagement (Robinson et al, 2015).…”
Section: The "Motor Challenging Physical Activity" Componentsupporting
confidence: 88%
“…Consistent with these findings, another recent study reported a decrease in the expression of OT receptor in peripheral blood cells of mothers maltreated during childhood, although no differences could be identified in baseline plasmatic OT between maltreated and non-maltreated individuals (95). For maltreated mothers, expression of OT receptors correlated negatively with Childhood Trauma scores (95). Dynamic changes in OT receptor methylation in response to psychosocial stress have been reported as well (96,97).…”
Section: Accepted Manuscriptmentioning
confidence: 64%
“…Indeed, recent work has demonstrated that low maternal care is associated with increased OT receptor promoter methylation levels, a process which typically represses gene expression (94). Consistent with these findings, another recent study reported a decrease in the expression of OT receptor in peripheral blood cells of mothers maltreated during childhood, although no differences could be identified in baseline plasmatic OT between maltreated and non-maltreated individuals (95). For maltreated mothers, expression of OT receptors correlated negatively with Childhood Trauma scores (95).…”
Section: Accepted Manuscriptmentioning
confidence: 72%